2018
DOI: 10.1007/s00412-018-0671-z
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of nuclear heterochromatin distribution during early development in the rabbit

Abstract: Changes to the spatial organization of specific chromatin domains such as constitutive heterochromatin have been studied extensively in somatic cells. During early embryonic development, drastic epigenetic reprogramming of both the maternal and paternal genomes, followed by chromatin remodeling at the time of embryonic genome activation (EGA), have been observed in the mouse. Very few studies have been performed in other mammalian species (human, bovine, or rabbit) and the data are far from complete. During th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…As for mammalian embryos, 3D-FISH approaches have been extensively used to demonstrate that pericentromeric regions, comprising minor and major satellite sequences (Guenatri et al, 2004), undergo large-scale reorganization during early embryonic development (reviewed by Jansz and Torres-Padilla, 2019). We and others have shown that dramatic changes occur throughout the two first cell cycles of mouse preimplantation development concomitantly with the onset of embryonic genome activation (EGA) (Aguirre-Lavin et al, 2012;Bonnet-Garnier et al, 2018;Probst et al, 2007). This spatial reorganization of heterochromatin was shown to be required for further development (Casanova et al, 2013;Probst et al, 2010), highlighting its importance.…”
Section: Introductionmentioning
confidence: 99%
“…As for mammalian embryos, 3D-FISH approaches have been extensively used to demonstrate that pericentromeric regions, comprising minor and major satellite sequences (Guenatri et al, 2004), undergo large-scale reorganization during early embryonic development (reviewed by Jansz and Torres-Padilla, 2019). We and others have shown that dramatic changes occur throughout the two first cell cycles of mouse preimplantation development concomitantly with the onset of embryonic genome activation (EGA) (Aguirre-Lavin et al, 2012;Bonnet-Garnier et al, 2018;Probst et al, 2007). This spatial reorganization of heterochromatin was shown to be required for further development (Casanova et al, 2013;Probst et al, 2010), highlighting its importance.…”
Section: Introductionmentioning
confidence: 99%
“…2 A . The bright puncta near the nuclear periphery are expected to be perinuclear heterochromatin as reported in the literature ( Politz et al, 2013 ), while bright foci inside the cell nucleus were expected to be repressive heterochromatin not actively transcribing ( Mutlu et al, 2018 , Bonnet-Garnier et al, 2018 ). After Pb treatment, we noticed significant reductions in both the number of bright foci and decrease in foci intensity, suggesting the potential onset of chromatin instability.…”
Section: Resultsmentioning
confidence: 57%
“…Previous reports have found that in human cells during differentiation, centromeres tend to move nearer to the nuclear periphery (Salníková et al, 2000; Bártová et al, 2001; Galiová et al, 2004; Horáková et al, 2010), or relocate more centrally (Bártová et al, 2008) to the heterochromatin surrounding nucleoli, and cluster together in chromo-centromeres (Alcobia et al, 2000; Beil et al, 2002). Movement of the centromeres toward the nuclear periphery was also observed in early rabbit embryos, once they had passed the 4-cell stage (Bonnet-Garnier et al, 2018). Such heterochromatic chromosomal regions may be more likely to be positioned toward the nuclear periphery which is supported by the findings of an increased association of chromatin silencing markers with perinuclear centromeres (Bártová et al, 2008) and with the under-acetylation of centromeres in both mouse and human undifferentiated cells (O'Neill and Turner, 1995; Keohane et al, 1996).…”
Section: How Aneuploidies Arisementioning
confidence: 85%